Dynamics of Changes in Oil Composition at the Development of the Usinsk Deposit; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Savinykh Yu. V. Yurii Valentinovich (2016, 2016)
Title screen